Strategi Pembelajaran Tahfizh Al-Qur’an pada Pendidikan Dasar melalui Metode Tikrar, Talaqqi, dan Visualisasi Ayat - Mulandi Mulandi; Aang Mahyani (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze tahfizh learning strategies in elementary education through the application of tikrar, talaqqi, and verse visualization methods. This study used a qualitative descriptive approach involving elementary school students participating in Qur’an memorization programs. Data were collected through observation, interviews, and documentation with tahfizh teachers and students. The results show that the use of tikrar (repetition), talaqqi and musyafahah, and verse visualization using a consistent mushaf contributes to better memorization practices, reading accuracy, and student engagement in memorizing the Qur’an. The use of memorization control books and structured murojaah also helps maintain students’ memorization consistency. The combination of these methods is more effective than using a single method because it is more suitable for the characteristics of students at the elementary education level.